Microbiota gut-brain axis: implications for pediatric-onset leukodystrophies - Vaia, Ylenia; Bruschi, Fabio; Tagi, Veronica Maria; Tosi, Martina; Montanari, Chiara; Zuccotti, Gianvincenzo; Tonduti, Davide; Verduci, Elvira (Frontiers in Nutrition, 2024)
Neurodegenerative disorders are a group of diseases characterized by progressive degeneration of the nervous system, leading to a gradual loss of previously acquired motor, sensory and/or cognitive functions. Leukodystrophies are amongst the most frequent childhood-onset neurodegenerative diseases and primarily affect the white matter of the brain, often resulting in neuro-motor disability.Notably, gastrointestinal (GI) symptoms and complications, such as gastroesophageal reflux disease (GERD) and dysphagia, significantly impact patients' quality of life, highlighting the need for comprehensive management strategies. Gut dysbiosis, characterized by microbial imbalance, has been implicated in various GI disorders and neurodegenerative diseases. This narrative review explores the intricate relationship between GI symptoms, Gut Microbiota (GM), and neurodegeneration. Emerging evidence underscores the profound influence of GM on neurological functions via the microbiota gutbrain axis. Animal models have demonstrated alterations in GM composition associated with neuroinflammation and neurodegeneration.Our single-centre experience reveals a high prevalence of GI symptoms in leukodystrophy population, emphasizing the importance of gastroenterological assessment and nutritional intervention in affected children. The bidirectional relationship between GI disorders and neurodegeneration suggests a potential role of gut dysbiosis in disease progression.Prospective studies investigating the GM in leukodystrophies are essential to understand the role of gutbrain axis dysfunction in disease progression and identify novel therapeutic targets.In conclusion, elucidating the interplay between GI disorders, GM, and neurodegeneration holds promise for precision treatments aimed at improving patient outcomes and quality of life.